2003
DOI: 10.1016/s0008-6363(03)00536-4
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial pacing induces memory and is associated with atrial tachyarrhythmias

Abstract: Pacing-induced impulse initiation from the left atrium alters the atrial gradient and is associated with atrial tachycardias. These changes in atrial gradient occur in the absence of ERP changes and may be early predictors of an arrhythmogenic substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…We recently hypothesized that a similar sensitivity to rare stimuli that alter atrial activation might help explain the effect of impulses originating in cardiac vessels to cause tachycardia/fibrillation in normal atria [10]. We based this hypothesis on two observations: (1) our own research indicating that atrial pacing at physiologic rates but from ectopic sites induces atrial electrophysiologic remodeling [11], atrial tachycardias and fibrillation [12], and (2) research by others indicating that bursting behavior in pulmonary veins and coronary sinus can initiate atrial fibrillation [4][5][6][7]. Both the pacing-induced arrhythmias and the ectopic activity in cardiac vasculature represent rare activity superimposed on the dominant activity characteristic of sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…We recently hypothesized that a similar sensitivity to rare stimuli that alter atrial activation might help explain the effect of impulses originating in cardiac vessels to cause tachycardia/fibrillation in normal atria [10]. We based this hypothesis on two observations: (1) our own research indicating that atrial pacing at physiologic rates but from ectopic sites induces atrial electrophysiologic remodeling [11], atrial tachycardias and fibrillation [12], and (2) research by others indicating that bursting behavior in pulmonary veins and coronary sinus can initiate atrial fibrillation [4][5][6][7]. Both the pacing-induced arrhythmias and the ectopic activity in cardiac vasculature represent rare activity superimposed on the dominant activity characteristic of sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…10 In many instances, an important factor in the initiation of AF is the presence of ectopic foci in the pulmonary veins. 11,12 Atrial ectopy, whether spontaneous, as with pulmonary venous foci, or paced, 13,14 often is a cause of altered atrial activation. We previously showed that pacing from sites that alter atrial activation induces a form of memory that is evident on surface ECG as a change in the atrial gradient.…”
mentioning
confidence: 99%
“…29 Left atrial (LA) pacing in mongrel dogs was associated with a decreased atrial gradient (the root mean square of three P-Ta voltage time integrals) and with occurrence of atrial tachycardias during pacing, that persisted during recovery from pacing. 50 This suggests that altering the atrial activation sequence induces atrial memory, without altering the AERP. In another study by Herweg et al displacement of the atrial gradient vector occurred during recovery from LA pacing, was more marked at rapid pacing rates, and manifested accumulation and resolution consistent with atrial cardiac memory.…”
Section: Remodelingmentioning
confidence: 99%